Modeling and computing magnetocaloric systems using the Python framework heatrapy. (October 2019) - Silva, D.J.; Amaral, J.S.; Amaral, V.S.
Highlights: Two magnetocaloric systems are modeled using the Heatrapy Python framework. Thermodynamic verification steps were used to validate a fully solid state model. The validation of a hydraulic model was done by comparing the results with literature. The described models require low memory usage and show fast computation. Abstract: Among all ferroic-based thermotechnologies, magnetocaloric refrigeration has become one of the most reported alternatives to vapor-compression systems. Hence, the modeling, and respective computation, of magnetocaloric systems has become of paramount importance in designing new devices. The need to optimize various adjustable model parameters makes overall computational costs a real-life limitation to these computational explorations. Recently, the heatrapy Python framework was made available, which aims at simulating caloric effects and thermal devices. In this work, two simple models are implemented in the heatrapy framework and are described and validated: one fully solid state magnetocaloric system, and one hydraulic active magnetic regenerative system. Both models show considerably reduced computational costs.